The Federation of Asian Bishops' Conferences (FABC) : bearing witness to the gospel and the reign of god in Asia - Tan, Jonathan Y. (Fortress Press, 2021)
"This book presents the theological contributions of the Federation of Asian Bishops' Conferences (FABC), a transnational body comprising fifteen Asian Catholic bishops' conferences as full members and ten associate members. The book introduces the contemporary context of Asia and represents a complete reworking of the author's approach to the FABC's way of being church and doing theology in Asia. The emphasis of the book is on the postcolonial dimensions of Asia and the challenges and implications of decolonization for shaping a postcolonial Asian church and way of theologizing. The book also addresses the challenges of religious pluralism for the FABC and the FABC's prophetic response--seeking to be a sacrament of unity and harmony amid much strife, violence, and conflict. Finally, the book discusses new challenges and possibilities for the FABC as it looks ahead. Tan explores the challenges and implications of migration, transient migration, online and virtual communities, and insider movements for shaping the future of the FABC's approach to theology." --